Implementation of Automatic Door Hand Code at PT. Medan Sugar Industry - Hartono Hartono; Silvia Lestari; Firman Syahputra (JUDIMAS, 2020)
The automatic door system is a system that is used to help human performance where this system uses hand-code collected from a set of data taken by using a camera in the form of an image. Therefore the researchers conducted research for hand-code recognition in making systems, doors. automatic. use skin tone detection and overall projection to recognize human hand codes, then convert them to binary "1" and "0" forms. The process is to use a web camera to automatically take a picture in the palm of someone's hand, then extract the feature by getting the important features from hand-code based on hand position. Perform tracking and projection integration to get the handheld functionality you need. So, it can be used to open and close doors automatically.